Caliphal Involvement in Water Provision in the Cities of the Early Abbasid Period - Bent, Josephine van den (Journal of Abbasid Studies, 2025)
Water management was crucial to the functioning of large early Islamic cities like Baghdad and Basra. In Abbasid-period sources, the caliph appears in multiple roles related to water management. This study investigates when and how caliphs became involved in water management during the early Abbasid period and examines these instances in light of the normative ideas communicated in taxation and governing manuals, among other sources. It also explores various factors that may have influenced caliphal decision-making with regard to water management.